2021
DOI: 10.2147/rmhp.s334611
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Providers’ Perception Towards Provision of Sexual and Reproductive Health Services for Unmarried Adolescents in Gamo Zone, Southern Ethiopia: A Phenomenological Study

Abstract: Background Healthcare providers play a critical role in the provision of sexual and reproductive health services for adolescents. In Ethiopia, due to different reasons, including healthcare providers associated reasons, most unmarried adolescents are not accessing the services. However, little is known about healthcare providers’ perception towards the provision of SRH services for unmarried adolescents. This study aimed to explore healthcare provider perception towards the provision of SRH servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…The ndings revealed that overall sexual and reproductive health service utilization was 27.4% (95%CI: 26.9, 27.8). This nding was higher than studies conducted in Gamo Gofa (16.9%) 15 Philippines (13.8%) 16 , Indonesia (24.3%) 17 East Gojam, Ethiopia (21.5%) 18 and Ethiopia 19.18%) 19 . However, lower than the study conducted in Jima Ethiopia, 41.1% 20 ; Eastern Ethiopia, 39.3% 21 ; Wolaita, Southern Ethiopia (49.8%) 22 and Kenya 36%) 23 .…”
Section: Discussioncontrasting
confidence: 57%
“…The ndings revealed that overall sexual and reproductive health service utilization was 27.4% (95%CI: 26.9, 27.8). This nding was higher than studies conducted in Gamo Gofa (16.9%) 15 Philippines (13.8%) 16 , Indonesia (24.3%) 17 East Gojam, Ethiopia (21.5%) 18 and Ethiopia 19.18%) 19 . However, lower than the study conducted in Jima Ethiopia, 41.1% 20 ; Eastern Ethiopia, 39.3% 21 ; Wolaita, Southern Ethiopia (49.8%) 22 and Kenya 36%) 23 .…”
Section: Discussioncontrasting
confidence: 57%
“…Similar findings were reported in studies from Senegal, Nigeria and Ethiopia, where healthcare providers tended to promote abstinence rather than providing contraceptive services to unmarried young populations. 14–16 Many studies have recognised provider bias: that is, providers’ self-imposed restrictions in order that young, unmarried people should not indulge in premarital sex. 26 These restrictions from providers do not comply with medical eligibility and are certainly against the clients’ rights.…”
Section: Discussionmentioning
confidence: 99%
“…Due to prevailing social norms for premarital sex, healthcare providers often feel uncomfortable discussing sexual issues with unmarried young people. 14 A study in Senegal reported that even when there were no legal restrictions, providers were reluctant to provide oral contraceptive pills to unmarried young women and advised them against premarital sex. 15 In Nigeria, healthcare providers perceived the provision of contraceptives for unmarried adolescents as promoting sexual promiscuity.…”
Section: Introductionmentioning
confidence: 99%
“…These situations are common to numerous African countries. In Ethiopia, Sidamo et al 30 observe the influence of sociocultural and religious norms on health workers' attitudes toward unmarried adolescents, which compromises SRH services delivery, already undermined by the health system's shortcomings in terms of essential medical supplies and training.…”
Section: Health Professionals Who Adhere To Social Normsmentioning
confidence: 99%